UPAYA DALAM MENINGKATAN PERTUMBUHAN TANAMAN SAWI HIJAU (Brassica juncea L.) DENGAN PEMBERIAN PUPUK ORGANIK CAIR - Giska Oktabriana (LPPM Universitas Malikussaleh – Indonesia, 2017)
Research Efforts in improving plant growth green mustard (Brassica juncea l.) byadministering aliquid organic fertilizer. The purpose of the research was to see theinfluence of organic cair fertilizer in increasing plant growth mustard greens. Researchusing Randomized Complete Design (RAL) consisting of 5 treatments and 3 replicates,so that there are 15 units of the experiment with the composition: A = control (withoutliquid organic fertilizer), B = 0.25 liter of liquid organic fertilizer/plot + 0.5 liters of water,C = 0.50 litres liquid organic fertilizer/plot + 1 litre water, D = 0.75 liters of liquid organicfertilizer/plot + 1.5 liters of water, E = 1 litre of liquid organic fertilizer/plot + 2 liters ofwater. From the results of research that has been done, it can be concluded the giving ofLiquid Organic Fertilizer (POC) cow blood wastes provide an impact on plantcolonization Mustard green.